Family history of skin cancer is associated with early-onset basal cell carcinoma independent of MC1R genotype. Issue 6 (December 2015) - Berlin, Nicholas L.; Cartmel, Brenda; Leffell, David J.; Bale, Allen E.; Mayne, Susan T.; Ferrucci, Leah M.
Highlights: Studies of familial skin cancer and basal cell carcinoma (BCC) are limited. BCC risk varied by cancer type and age of onset of familial skin cancer. The family history association was not explained by lifestyle or behavioral factors. Evaluating family history may aid in assessing risk of early-onset BCC. Abstract: Background: As a marker of genetic susceptibility and shared lifestyle characteristics, family history of cancer is often used to evaluate an individual's risk for developing a particular malignancy. With comprehensive data on pigment characteristics, lifestyle factors, and melanocortin 1 receptor ( MC1R ) gene sequence, we sought to clarify the role of family history of skin cancer in early-onset basal cell carcinoma (BCC). Materials and methods: Early onset BCC cases ( n = 376) and controls with benign skin conditions ( n = 383) under age 40 were identified through Yale dermatopathology. Self-report data on family history of skin cancer (melanoma and non-melanoma skin cancer), including age of onset in relatives, was available from a structured interview. Participants also provided saliva samples for sequencing of MC1R . Results: A family history of skin cancer was associated with an increased risk of early-onset BCC (OR 2.49, 95% CI 1.80–3.45). In multivariate models, family history remained a strong risk factor for early-onset BCC after adjustment for pigment characteristics, UV exposure, and MC1R genotype (OR 2.41, 95% CI 1.74–3.35). Conclusions: Risk for BCC varied based upon the type and age of onset of skin cancer among affected relatives; individuals with a first-degree relative diagnosed with skin cancer prior to age 50 were at highest risk for BCC (OR 4.79, 95% CI 2.90–7.90). Even after taking into account potential confounding effects of MC1R genotype and various lifestyle factors that close relatives may share, family history of skin cancer remained strongly associated with early-onset BCC.